2004
DOI: 10.1016/j.materresbull.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tungsten trioxide powders prepared from tungstic acids

Abstract: WO 3 powders were prepared by the thermal decomposition of tungstic acids (WO 3 ÁnH 2 O, n ¼ 1/3, 1, 2). The tungstic acids were synthesized from WO 4 2À aqueous solutions under a variety of conditions of pH, temperature and W(VI) concentrations. The thermal decomposition of the tungstic acids into WO 3 was analysed by TG and DSC methods. Nano-sized WO 3 powders with different morphological characteristics were obtained by thermal treatment of the tungstic acids at 500 8C in air atmosphere. The morphologies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 28 publications
(44 reference statements)
1
28
0
1
Order By: Relevance
“…Most of these hydrated compounds are prepared through solution routes, and a large amount of literature is available on the preparation and characterization of these compounds (Gerand et al 1981). Recently, a detailed study of tungsten oxide powders prepared from different tungstic acids has been reported (Nogueira et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these hydrated compounds are prepared through solution routes, and a large amount of literature is available on the preparation and characterization of these compounds (Gerand et al 1981). Recently, a detailed study of tungsten oxide powders prepared from different tungstic acids has been reported (Nogueira et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The CaWO 4 :Eu 3+ phosphor has approximate vibration modes as the CaMoO 4 :Eu 3+ phosphor. Report on the FT-IR property of tungstate acids by Jesus et al[27] shows that both have five vibrations modes, as described inTable 1. The bands at 3454 cm À1 and 1630.7 cm -1 are assigned to O-H stretching vibration and H-O-H bending vibration[4], respectively.…”
mentioning
confidence: 99%
“…2b) decreases significantly along with the appearance of the diffraction pattern of WO 3 (JCPDS-ICDD File No. 43-1035), suggesting that the dehydration of WO 3 Á H 2 O occurred at 400°C and formed WO 3 phase [28]. The diffraction peaks (020)/(200) and (202)/(220) of WO 3 were maintained in the sample of Pt-WO 3 /MWCNT ao after Pt deposition, as displayed in Fig.…”
Section: Physicochemical Characterization Of the As-prepared Catalystsmentioning
confidence: 80%